Leaf water potential as an indicator of water deficit in maize - Bergonci, João Ito (2000)
This study was carried out at the Agronomic Experimental Station of the Federal University of Rio Grande do Sul, in Eldorado do Sul, RS, Brazil, during the agricultural seasons of 1993/94 and 1994/95. The objective was to evaluate the leaf water potential as an indicator of the water deficit in maize (Zea mays L.), and its relation with the soil water potential. The experiment comprised three levels of irrigation, from field capacity to absence of irrigation. The values of the minimum leaf water potential ranged from -1.2 to -1.5 MPa in irrigated plants (field capacity) and from -1.6 to -2.0 MPa in nonirrigated plants. The minimum leaf water potential was well correlated to the matric water potential measured at 45 cm deep (r2 = 0.73). The sunset leaf water potential showed relationship with the minimum leaf water potential indicating it to be an indicator of water deficit. The predawn leaf water potential showed clear differences between the utmost treatments, but did not show any consistent relationship with the minimum leaf water potential.